2013
DOI: 10.4103/2279-042x.117385
|View full text |Cite
|
Sign up to set email alerts
|

A survey on the factors influencing the pattern of medicine′s use: Concerns on irrational use of drugs

Abstract: Objective:Pharmacists have a remarkable role in rational use of drugs by dissemination of drug information to guide patients, physicians, and policy makers. The present study was undertaken to evaluate the pharmacists’ view point about the main factors affecting current drug use pattern regarding rational drug use and the most effective strategies for improving and promoting rational drug use among pharmacists.Methods:In a cross-sectional survey, pre-designed questionnaires were filled in convenient sampling b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…A total of 7 studies investigated effective factors on irrational prescription of medicine (27,30,(35)(36)(37)(38)41). Akkerman et al in a study, assessed determining factors of over-prescribing of antibiotics using the Dutch national guidelines as a benchmark.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 7 studies investigated effective factors on irrational prescription of medicine (27,30,(35)(36)(37)(38)41). Akkerman et al in a study, assessed determining factors of over-prescribing of antibiotics using the Dutch national guidelines as a benchmark.…”
Section: Resultsmentioning
confidence: 99%
“…Soleymani et al in a cross-sectional study, used a pre-designed questionnaire in a convenient sampling of pharmacists to analyze the pharmacists' viewpoints about the main factors of rational use of medicine and reported that the most important determinant was the lack of public knowledge and awareness about the appropriate use of medicines (38).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous qualitative study, the strategies for the prevention of induced demand for medicine prescription were classified into two categories of health educational programs and stewardship in the healthcare system [9]. Several studies have also confirmed that increased levels of information in patients [12,[14][15][16][17], informing patients and their families on disease diagnosis and treatment [10], prioritization of health educational programs regarding the irrational use of medicines [18], and policymaking and setting regulations for the prevention of SID in healthcare providers are essential to the control of induced demand for medicine prescription [10,19]. In the aforementioned studies, no data have been proposed regarding the rate of the consequences of this issue its causes.…”
Section: Introductionmentioning
confidence: 99%